2022
DOI: 10.1108/jkm-09-2021-0681
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting e-government adoption in the UAE public sector organisations: the knowledge management perspective

Abstract: Purpose This study aims to investigate factors that influence e-government adoption among public sector departments with the view to determine how such factors may be used to better facilitate e-government adoption across United Arab Emirates (UAE) public sectors. The use of e-government is advocated for the central government in the UAE. Design/methodology/approach Using random sampling, a total of 172 participants from ten departments and organisations in Dubai and Sharjah completed the online survey for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“… [ 42 ]. Resource-based view (RBV) theory [ 53 , 12 , 46 ] Groups and organizations This theory promote how to manage rare and difficult to imitate resources for organization improvements in the public sectors and assist how to make a decision within the sectors [ 29 ]. Behavioral theory [ 26 ] Individuals This theory helps to understand the workers behavior how to fit with the expected outcomes and how to share knowledge within the group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [ 42 ]. Resource-based view (RBV) theory [ 53 , 12 , 46 ] Groups and organizations This theory promote how to manage rare and difficult to imitate resources for organization improvements in the public sectors and assist how to make a decision within the sectors [ 29 ]. Behavioral theory [ 26 ] Individuals This theory helps to understand the workers behavior how to fit with the expected outcomes and how to share knowledge within the group.…”
Section: Resultsmentioning
confidence: 99%
“… [ 64 ]. Unified theory of acceptance and use of technology (UTAUT) [ [29] , [68] ] Organization This theory enables to predict the performance of public sectors by adopting knowledge based utilizations of technology in different public sectors [ 51 ]. Two-sided market theory [ 57 ] Organization Tow sided market theory enables to create dynamic links between imagery and very specific information to respond to end-user requirement and create high added value such as the social value for a whole community through the transfer of innovation and efficiency in the implementation of public policy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that knowledge of people influences to various extents, their adoption behaviour (de Kok et al, 2020;Al Sayegh et al, 2023). Adequate knowledge of the important characteristics of an innovation or agricultural technology can thus play an important role in helping prospective adopters make the right decision about the technology.…”
Section: Knowledge Of Improved Rice Varieties Characteristicsmentioning
confidence: 99%
“…In the contemporary working environment, public sector employees are expected to possess a comprehensive understanding of computer technology in order to actively engage and contribute to their professional roles. Al Sayegh et al, (2023) noted that the level of computer literacy among the population plays a significant role in the effectiveness of electronic government implementation. The Tanzanian government has been proactively implementing electronic government (e-Government) initiatives with the aim of improving the effectiveness, openness, and availability of public services.…”
Section: Introductionmentioning
confidence: 99%